Effectiveness of anticholinergic drugs compared with placebo in the treatment of overactive bladder: systematic review. Issue 7394 (19th April 2003) - Herbison, Peter; Hay-Smith, Jean; Ellis, Gaye; Moore, Kate
Abstract: Objective: To determine the effectiveness of anticholinergic drugs for the treatment of overactive bladder syndrome. Design: Systematic review of randomised controlled trials. Data sources: Published papers and abstracts. Study selection: Randomised controlled trials with anticholinergic drug treatment in one arm and placebo in another. Data extraction: Primary outcomes of interest were patient perceived cure or improvement in symptoms, differences in number of incontinent episodes and number of voids in 24 hours, and side effects. Secondary outcomes of interest were urodynamic measures of bladder function (volume at first contraction, maximum cystometric capacity, and residual volume) and adverse events. Data synthesis: 32 trials were included, totalling 6800 participants. Most trials were described as double blind but were variable in other aspects of quality. At the end of treatment, cure or improvement (relative risk 1.41, 95% confidence interval 1.29 to 1.54), differences in incontinent episodes in 24 hours (estimated mean difference 0.6, 0.4 to 0.8), number of voids in 24 hours (0.6, 0.4 to 0.8), maximum cystometric capacity (54 ml, 43 ml to 66 ml), and volume at first contraction (52 ml, 37 ml to 67 ml), were significantly in favour of anticholinergics (P<0.0001 for all). Anticholinergics were associated with significantly higher residual volumes (4 ml, 1 ml to 7 ml; P=0.02) and an increased rate of dry mouth (relative risk 2.56, 2.24 to 2.92; P<0.0001). Sensitivity analysis, although affected by small numbers of studies, showed little likelihood of an effect of age, sex, diagnosis, or choice of drug. Conclusions: Although statistically significant, the differences between anticholinergic drugs and placebo were small, apart from the increased rate of dry mouth in patients receiving active treatment. For many of the outcomes studied, the observed difference between anticholinergics and placebo may be of questionable clinical significance. None of these studies provided data on long term outcome.